Empirical and thermal resistance approaches for debris thickness estimation on the Hoksar Glacier, Kashmir Himalaya - Ali, Iram; Shukla, Aparna; Romshoo, Shakil A.; Lone, F. A.; Garg, Purushotum K.; Yousuf, Bisma (Frontiers in Water, 2024)
Supraglacial debris modulates the thermal regime and alters glacial melt rates depending on its thickness. Thus, the estimation of debris thickness becomes imperative for predicting the hydrological response and dynamics of such glaciers. This study tests the performance of empirical and thermal resistance-based debris thickness approaches against field measurements on the Hoksar Glacier, Kashmir Himalaya. The aim of this study was accomplished using thermal imageries (Landsat 8 Operational Land Imager [Landsat-OLI], 2017 and Advanced Spaceborne Thermal Emission and Reflection Radiometer [ASTER] Surface Kinetic Temperature Product [AST08], 2017) and the European Centre for Medium-Range Weather Forecasts (ECMWF) Reanalysis v5 (ERA-5) datasets. First, the spatially resolved estimates of debris thickness for the entire debris-covered zone were achieved by establishing an empirical relationship between debris thickness and debris surface temperature (both field and satellite thermal imageries). Second, debris thickness for every pixel of thermal imagery was executed by calculating thermal resistance from the energy balance model incorporating primary inputs from (ERA-5), debris temperature (AST08, Landsat OLI), and thermal conductivity. On comparison with field temperature and thickness measurements with satellite temperature, homogenous debris thickness pixels showed an excellent coherence (r = 0.9; p < 0.001 for TAST08 and r = 0.88; p < 0.001 for TLandsat OLI for temperature) and (r = 0.9; p < 0.001 for TAST08 and r = 0.87; p < 0.002 for TLandsat OLI for debris thickness). Both approaches effectively captured the spatial pattern of debris thickness using Landsat OLI and AST08 datasets. However, results specify an average debris thickness of 18.9 ± 7.9 cm from the field, which the empirical approach underestimated by 12% for AST08 and 28% for Landsat OLI, and the thermal resistance approach overestimated by 6.2% for AST08 and 5.1% for Landsat OLI, respectively. Debris thickness estimates from the thermal resistance approach (deviation 11.2% for AST08 and 11.6% for Landsat OLI) closely mirror the field measurements compared to the empirical approach (deviation 26.9% for AST08 and 35% for Landsat OLI). Thus, the thermal resistance approach can solve spatial variability in debris thickness on different heavily debris-covered glaciers globally without adequate knowledge of field measurements.